Blaze and the monster machines. High-speed adventures [videorecording (DVD)]. (Viacom, 2015)
Let's blaaaze into four high-speed races with the Monster Machines! Help Blaze and AJ use adhesion to stop Zeg from bouncing away and acceleration to get Darington to the Stuntmania Super Track. Plus, win a sailboat race with the right parts and wind power, and even team up with Pickle for Team Truck Challenge Day!